An accurate and efficient time-domain model for simulating water-cylinder dynamic interaction during earthquakes. (1st July 2018) - Wang, Piguang; Zhao, Mi; Li, Huifang; Du, Xiuli
Highlights: A time-domain model simulating the water-cylinder interaction is presented. The exact dynamic stiffness relationship is obtained based on the exact solution. The relationship is transformed into a high-order approximation in time domain. The proposed model is implemented into software ABAQUS by the UEL subroutine. Abstract: Seismic analysis of many offshore structures is the three-dimensional (3D) water-cylinder dynamic interaction. The cylinder is commonly modeled as a beam by finite elements. If the 3D infinite water layer is also modeled by the finite elements, the high computational costs are unacceptable in engineering practice. Therefore, an accurate and efficient time-domain model is proposed to replace the 3D infinite water layer in the water-cylinder interaction analysis. Firstly, based on the frequency-domain analytical solution, the exact dynamic stiffness relationship between the hydrodynamic pressure and the structural displacement is constructed on the water-cylinder interface. Secondly, this relationship is transformed into a high-order approximation in time domain by using the temporal localization method. Thirdly, the high-order approximation is represented as a mechanical model system consisting of the spring, dashpot and mass elements, which is implemented into the finite element software ABAQUS by the user element subroutine. Finally, numerical examples are given to indicate the effectiveness of the proposed time-domain model and investigate the effect of hydrodynamic pressure on the seismic responses of the cylinder.